Physician training protocol within the WEB Intrasaccular Therapy (WEB-IT) study. (16th August 2017) - Arthur, Adam; Hoit, Daniel; Coon, Alexander; Delgado Almandoz, Josser E; Elijovich, Lucas; Cekirge, Saruhan; Fiorella, David
Abstract : Introduction: The WEB Intra-saccular Therapy (WEB-IT) trial is an investigational device exemption study to demonstrate the safety and effectiveness of the WEB device for the treatment of wide-neck bifurcation aneurysms. The neurovascular replicator (Vascular Simulations, Stony Brook, New York, USA) creates a physical environment that replicates patient-specific neurovascular anatomy and hemodynamic physiology, and allows devices to be implanted under fluoroscopic guidance. Objective: To report the results of a unique neurovascular replicator-based training program, which was incorporated into the WEB-IT study to optimize technical performance and patient safety. Methods: US investigators participated in a new training program that incorporated full surgical rehearsals on a neurovascular replicator. No roll-in cases were permitted within the trial. Custom replicas of patient-specific neurovascular anatomy were created for the initial cases treated at each center, as well as for cases expected to be challenging. On-site surgical rehearsals were performed before these procedures. Results: A total of 48 participating investigators at 25 US centers trained using the replicator. Sessions included centralized introductory training, on-site training, and patient-specific full surgical rehearsal. Fluoroscopy and procedure times in the WEB-IT study were not significantly different from those seen in two European trials where participating physicians had significant WEB procedure experience before study initiation. Conclusions: A new program of neurovascular-replicator-based physician training was employed within the WEB-IT study. This represents a new methodology for education and training that may be an effective means to optimize technical success and patient safety during the introduction of a new technology.